Evolving the Role of Discovery-focused Pathologists and Comparative Scientists in the Pharmaceutical Industry. (February 2019) - Mohanan, Sunish; Maguire, Sean; Klapwijk, Jan; Adler, Rick; Haworth, Richard; Clements, Peter
GlaxoSmithKline has recently made significant organizational changes to its nonclinical safety, drug metabolism and pharmacokinetic, and laboratory animal science/veterinary functions, with the goal to increase our focus on scientific partnership with the discovery part of the organization. One specific change was bringing together pathologists and comparative medicine veterinarians and scientists into a single functional unit. We describe our early activities (assessing our capabilities and gaps, external benchmarking, listening to our discovery partners, redesigning some of our working practices) aimed at implementing these changes. In addition, early on we held a Discovery Engagement Workshop attended by all pathologists and comparative medicine veterinarians and scientists, as well as selected discovery scientists. The purpose of this workshop was to share learnings from the above activities and devise plans aimed at achieving our overall goal of functional integration: driving pathobiology expertise into drug discovery and increasing the human (translational) relevance of experimental data. This review describes the new organizational structure, the workshop activities, and implementation plans; updates our progress; and considers the opportunity for a pan-industry network of discovery-focused pathologists and comparative medicine veterinarians and scientists.